FINANNCIAL FEASIBILITY ANALYSIS OF MOJOSARI LAYING DUCK BREEDING FARM WITH INTENSIVE REARING SYSTEM - T., Isadora; Putri, B. R. T.; Sukanata, I W. (Jurnal Peternakan Tropika; Vol 6 No 1 (2018): Vol. 6 No. 1 (2018), 2018)
This research aims to determine the management of maintenance, marketing, and analyze the financial feasibility of duck breeding farms with intensive rearing system. This research was conducted from May to June 2017 at UD. Sinar Harapan located at Kedawung Village, Blitar Regency, East Java. The data used were primary and secondary data. The variables observed in this study are the company's general overview, livestock raising management, cost flow, financial feasibility analysis, and business sensitivity. The financial feasibility level of this business was determined based on the analysis of investment criteria, Pay Back Period analysis, Break Even Point, and sensitivity analysis. Business duck breeding mojosari of UD. Sinar Harapan was very concerned for several aspects, i.e. the selection of going, ranching, feeding, prevention and treatment of diseases, labor, and marketing. The results of this research showed that this business produced NPV for Rp 9.484.255.062 IRR for 167,07%, Net B/C for 5,53, Pay Back Period for 0,95 year, and Break Even Point happened in 1,49 year. Sensitivity analysis results showed that this business was sensitive to change in the selling price of egg was 37,98%. Sensitivity analysis results showed that this business was less sensitive to the increase of feed price for 92,24%. Thus, duck breeding farming business mojosari of UD. Sinar Harapan was financially feasible. Keywords: Laying Duck Farming, Mojosari Duck, Intensive Rearing System, Financial Feasibility